Strain-Enabled Band Structure Engineering in Layered PtSe2 for Water Electrolysis under Ultralow Overpotential - Jeon, Hotae; Kwon, Hee Jung; Lee, Jaehyun; Han, Sun Kyung; Kim, Hyunjin; Heo, Jaewon; Han, Junhwi; Shin, Seunghun; Park, Jiheon; Cho, Min Kyung; Preston, Daniel J.; Kim, In Soo; et al. (American Chemical Society, 2025)
This paper describes a simple design methodology to develop layered PtSe2 catalysts for hydrogen evolution reaction (HER) in water electrolysis operating under ultralow overpotentials. This approach relies on the transfer of mechanically exfoliated PtSe2 flakes to gold thin films on prestrained thermoplastic substrates. By relieving the prestrain, a tunable level of uniaxial internal compressive and tensile strain is developed in the flakes as a result of spontaneously formed surface wrinkles, giving rise to band structure modulations with overlapped values of the valence band maximum and conduction band minimum. This strain-engineered PtSe2 with an optimized level of internal tensile strain amplifies the HER performance of the PtSe2, with performance far greater than that of pure platinum due to significantly reduced charge transfer resistance. Density functional theory calculations provide fundamental insight into how strain-induced band structure engineering correlates with the promoted HER activity, especially at the atomic edge sites of the materials.